Motif Penggunaan Game Online Roblox pada Anak Usia Sekolah - Tivani Yuliastika; Mayasari Mayasari; Ana Fitriana Poerana (Peneliti.net, 2023)
The purpose of this research is to find the motive or urge behind the high interest of the Roblox online game in school age children. This research uses the qualitative method with phenomenology approach. The subject of this research are five children with one year Roblox experience. The result of the research analyzed by Alfred Schutz's phenomenologycal theory and shows that the because motive of the use of Roblox online game is due to the influence of ads and Youtube videos, curiosity that stems from visual similarities with previous games experience, and the fear of missing out. The in order to motive of the informant is to increase skill, to travel in real life someday like in the game, to find new friends, and to have their own laptop to access Roblox Studio and make their own game. The meaning of using Roblox online game for children is the meaning of entertainment and the meaning of togetherness.